Associations of serum insulin-like growth factor-I and insulin-like growth factor-binding protein 3 levels with biomarker-calibrated protein, dairy product and milk intake in the Women's Health Initiative. Issue 5 (14th March 2014) - Beasley, Jeannette M.; Gunter, Marc J.; LaCroix, Andrea Z.; Prentice, Ross L.; Neuhouser, Marian L.; Tinker, Lesley F.; Vitolins, Mara Z.; Strickler, Howard D.
<x content-type="archive" xml:space="preserve">Abstract</x> It is well established that protein–energy malnutrition decreases serum insulin-like growth factor (IGF)-I levels, and supplementation of 30 g of whey protein daily has been shown to increase serum IGF-I levels by 8 % after 2 years in a clinical trial. Cohort studies provide the opportunity to assess associations between dietary protein intake and IGF axis protein levels under more typical eating conditions. In the present study, we assessed the associations of circulating IGF axis protein levels (ELISA, Diagnostic Systems Laboratories) with total biomarker-calibrated protein intake, as well as with dairy product and milk intake, among postmenopausal women enrolled in the Women's Health Initiative (n 747). Analyses were carried out using multivariate linear regression models that adjusted for age, BMI, race/ethnicity, education, biomarker-calibrated energy intake, alcohol intake, smoking, physical activity and hormone therapy use. There was a positive association between milk intake and free IGF-I levels. A three-serving increase in milk intake per d (approximately 30 g of protein) was associated with an estimated average 18·6 % higher increase in free IGF-I levels (95 % CI 0·9, 39·3 %). However, total IGF-I and insulin-like growth factor-binding protein 3 (IGFBP-3) levels were not associated with milk consumption and nor were there associations between biomarker-calibrated protein intake, biomarker-calibrated energy intake, and free IGF-I, total IGF-I or IGFBP-3 levels. The findings of the present study carried out in postmenopausal women are consistent with clinical trial data suggesting a specific relationship between milk consumption and serum IGF-I levels, although in the present study this association was only statistically significant for free, but not total, IGF-I or IGFBP-3 levels.